Exploring the consequences of knowledge hiding: an agency theory perspective. Issue 2 (18th February 2020) - Khoreva, Violetta; Wechtler, Heidi
Abstract : Purpose: The purpose of the study is to explore empirically the consequences of knowledge hiding at the individual level and from the knowledge hiding committers' perspective. Hence, in line with agency theory and prior literature on knowledge hiding, the study investigates the associations between different facets of knowledge hiding and individual-level job performance, as well as the mediating role of employee well-being in the associations. Design/methodology/approach: Structural equation modeling was used to analyze multisource survey data from a sample of 214 employees and 34 immediate supervisors, in a professional services company in Finland. Findings: Evasive hiding was found to be negatively associated with in-role job performance and positively associated with innovative job performance. Playing dumb was found to be positively associated with in-role job performance. Finally, even though the association between rationalized hiding and innovative job performance was found to be positive, it was found to be of a smaller magnitude when employee well-being was taken into account. Practical implications: Forceful unhealthy competition and exploitative and workaholic cultures are discussed to reduce knowledge hiding behavior among employees and their negative consequences. Originality/value: The study highlights the paradox of managing organizational knowledge. In line with agency theory, we advocate that while knowledge sharing is one of the major assets of organizational welfare from the organizational perspective, it may resonate with the employee's perspective. Consequently, unless employees' self-interest and organizational interests are aligned, the paradox of managing organizational knowledge arises, and the classic agency problem occurs.